Desenvolvimento de um oftalmoscópio binocular indireto com sistema eletrônico cromático de iluminação e módulo de aquisição de imagens - Oliveira, Thiago Bellini (2009)
Chromatic contrast is a technique used in some areas of medicine to provide better visualization of biological tissues. Based on principles of color composition, a new illumination system was constructed using colored emitting diodes to reproduce the spectral range of the visible light. This technique was devised to be used into indirect ophthalmoscopes to improve the visualization of the posterior segment of the eye.